Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1002/cncr.11796
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tenascin‐C in various human brain tumors and its relevance for survival in patients with astrocytoma

Abstract: BACKGROUNDTenascin‐C (TN‐C), a large extracellular matrix (ECM) glycoprotein with a molecular weight of 180–250 kilodaltons, is present in several normal adult tissues. TN‐C is up‐regulated during embryogenesis, in wound healing, and in tumor tissues. Glioblastoma multiforme (GBM) is the most frequent and malignant astrocytic tumor comprised of poorly differentiated, neoplastic astrocytes. Recently, TN‐C‐based radioimmunotherapy was administered to patients with GBM.METHODSIn the current study, the authors use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 40 publications
7
87
1
3
Order By: Relevance
“…The identification of tenascin-C as a facilitatory factor for glioma invasiveness in a three-dimensional matrix is relevant because it is increased in brain tumors where its expression increases with tumor grade (15,16,18,20,38). In vitro studies have found that tenascin-C increases the migration of glioma cells in monolayer or spheroid cultures (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of tenascin-C as a facilitatory factor for glioma invasiveness in a three-dimensional matrix is relevant because it is increased in brain tumors where its expression increases with tumor grade (15,16,18,20,38). In vitro studies have found that tenascin-C increases the migration of glioma cells in monolayer or spheroid cultures (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In malignant gliomas, many ECM components are overexpressed both in the tumor stroma and at the advancing edge of the tumor within brain parenchyma. These ECM molecules include vitronectin, collagen I, collagen IV, osteopontin, tenascin-C, secreted protein acidic and rich in cysteine, and brain enriched hyaluronan binding (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Glioma invasion is thought to occur along ECM protein-containing structures, such as along tracts of myelinated fibers (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…TN-C is characterized by its regulated expression and by its cell adhesion modulatory function (14,15). Constitutive expression of TN-C has been observed in lymphoid tissues, such as adult bone marrow and lymph nodes (16,17), whereas it is transiently expressed in pathological states, including inflammation and tumorigenesis (18,19). Therefore, lymphoid tissues of patients with hematopoietic malignancy have highly increased expression of TN-C. TN-C acts as both an adhesive and an antiadhesive substrate, depending on the cellular context (20).…”
mentioning
confidence: 99%
“…TNC is early described as a stormal marker associated with malignant behavior of breast cancer (Mackie et al, 1987). In addition, TNC is highly expressed in brain tumor (Leins et al, 2003), head and neck cancers (Lyons et al, 2007;Atula et al, 2003). In the above described tumors, the high expression TNC is associated with invasion and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%